INHERITANCE LAWS AND GENDER EQUALITY IN BANGLADESH: A CRITICAL ANALYSIS WITH POLICY RECOMMENDATIONS (Lex localis - Journal of Local Self-Government, 2025)
Inheritance laws shape the distribution of wealth, power, and social status. In Bangladesh, these laws are largely determined by personal laws based on religion, which often disadvantage women. Despite constitutional guarantees of equality and international commitments to women’s rights, the inheritance regime reflects structural inequalities that perpetuate gender-based discrimination. This research paper critically examines the existing inheritance laws in Bangladesh, their implications for gender equality, and their conflicts with constitutional and international human rights standards. Drawing upon doctrinal legal research, comparative jurisprudence, and policy analysis, the study identifies legal, social, and institutional gaps and proposes a set of policy recommendations aimed at ensuring fair inheritance rights for women. The findings reveal a persistent tension between religious personal laws and constitutional obligations, and highlight the urgent need for reform to achieve substantive gender equality.